2020
DOI: 10.1021/acs.jchemed.0c00376
|View full text |Cite
|
Sign up to set email alerts
|

Using a Faculty-Developed Documentary-Style Film to Communicate Authentic Chemistry Research to a High School Audience

Abstract: Described is the creation, deployment, and evaluation of a video produced about the synthesis and applications of metal–organic frameworks (MOFs). The goal of this project was to gauge the impact of viewing the video on high school students’ conceptions of authentic chemistry practices and applications. Additionally, comparisons were made between the use of the video and more traditional face-to-face presentations given by professional scientists. Observations, student surveys, and an interview with the high s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…In this scenario, it is clear that videos have been widely used in classes to improve learning, assist in laboratory classes, and even to disseminate chemistry in a fun way, but with regard to the dissemination of scientific research carried out by universities, there are few reports of this type of disclosure, such as the works of Burgin et al, 30 that evaluated the impact of viewing a video produced on the synthesis and applications of metal−organic structures (MOFs) on high school students' conceptions of authentic chemistry practices and applications. The authors found that students who watched the video reported learning more about the nature of laboratory work in chemistry than other students who did not watch the video.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In this scenario, it is clear that videos have been widely used in classes to improve learning, assist in laboratory classes, and even to disseminate chemistry in a fun way, but with regard to the dissemination of scientific research carried out by universities, there are few reports of this type of disclosure, such as the works of Burgin et al, 30 that evaluated the impact of viewing a video produced on the synthesis and applications of metal−organic structures (MOFs) on high school students' conceptions of authentic chemistry practices and applications. The authors found that students who watched the video reported learning more about the nature of laboratory work in chemistry than other students who did not watch the video.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Luckily there are options to overcome this situation inside the classroom like gaming, music, movies, videos, digital content, and digital tools (TIC: communication and information technologies as translated from Spanish), among others. These strategies are under the title of educational innovation because they look to promote new educational methods in modern and diverse contexts according to present world challenges. In the same way, it is now possible to find digital educational and commercial platforms aimed at Chemistry learning with interesting and structured content like the Khan Academy, Quimitube, Chemspider, Educatina, and Químicaweb. However, most of these tools are not within the context and needs of schools in the region, especially within rural schools.…”
Section: Introductionmentioning
confidence: 99%
“…Through tunable modification of pore shape and size by varying the metal nodes and organic linker identity, MOFs function as an efficient system in which to engineer targeted molecular interactions to enable selective uptake and storage of a particular molecule such as CO 2 . , Although MOFs offer tremendous promise as materials for uptake and detection of gases, only a limited number of experiments have been developed to emphasize the fundamentals related to MOF synthesis and structure–property relationships at the high school and undergraduate levels. At the undergraduate level, models for experiments encompassing the synthesis and application of MOFs focus on teaching important chemical concepts, such as reticular synthesis, carbon capture and storage (CSS), , luminescence, lanthanide chemistry, and host–guest chemistry. , Specifically for cyclodextrin (CD)-based MOFs, there are only two undergraduate laboratory experiments with applications for CO 2 uptake and pollutant removal, and there are even fewer MOF-based experiments for high school students. , The experiments developed to date require access to laboratory infrastructure and specialized chemicals that are unsafe and inaccessible in home-based, resource-limited, or other remote-learning settings. The only resource currently available for remote instruction for MOF synthesis and application is video-based and does not offer students hands-on learning opportunities . To improve equality in the training of the future scientific community, enhance workforce development, and promote global scientific literacy in response to the challenges of remote and hybrid learning emphasized by a global pandemic, development of scientific experimental activities that can be performed without access to a laboratory or specialized chemicals is urgently needed.…”
mentioning
confidence: 99%
“…The only resource currently available for remote instruction for MOF synthesis and application is videobased and does not offer students hands-on learning opportunities. 29 To improve equality in the training of the future scientific community, enhance workforce development, and promote global scientific literacy in response to the challenges of remote and hybrid learning emphasized by a global pandemic, development of scientific experimental activities that can be performed without access to a laboratory or specialized chemicals is urgently needed. With MOFs bridging the divide between traditional disciplines of organic and inorganic chemistry, this class of materials provides an excellent opportunity to introduce students to the fundamentals of chemical coordination and porous materials, synthetic techniques such as vapor diffusion for crystal growth, and promote hands-on experience with applications in gas capture and host−guest chemistry.…”
mentioning
confidence: 99%